The Influence of e-glass epoxy composite laminate material application on the crack pattern of cylinder concrete column cross-section - Achmad Jusuf Zulfikar; Din Aswan A Ritonga; Ari Purnomo; Toni Erdiansyah; Ahmad Rivaldo (JTTM : Jurnal Terapan Teknik Mesin, 2024)
In order to better understand the phenomenon of applying GEC reinforcement to RCC based on the percentage of surface crack pattern (PCP), this research will use e-glass epoxy composite laminate (GEC) to obtain the damage pattern of reinforced concrete column specimens (RCC) utilizing GEC. Additionally, it will compare the splitting tensile strength (STS) and SCP. In accordance with ASTM C496 guidelines, the RCC specimens used in this investigation had a cylindrical shape and measured 150 mm in length and 50 mm in diameter. GEC material, consisting of 0–4 layers of woven e-glass fiber sheets, was applied as an extra layer on top of the RCC. In compliance with ASTM C496 guidelines, a Universal Testing Machine (UTM) was used to perform the split tensile test. With the aid of Adobe Photoshop software, the Histogram approach was used to calculate the crack pattern's proportion. The study's findings demonstrated that the specimens reinforced with four layers of GEC exhibited the highest damage pattern. This suggests that the reinforced specimens must be subjected to a sizable load in order to be damaged. Hence, the damage that occurs in the specimens can be lessened by applying GEC layers on RCC. Further information about the performance of RCC reinforced with GEC is also provided by a comparison of the splitting tensile strength and the percentage of fracture pattern